Strategi Peningkatan Kualitas Pembelajaran Berbasis Teknologi di Perguruan Tinggi Vokasi: Tinjauan terhadap Implementasi Platform Pembelajaran Online - Suyono Suyono (Departement of Mathematics Education, 2024)
This research aims to conduct an in-depth exploration of effective strategies in improving the quality of technology-based learning in vocational college environments, with a focus on the implementation of online learning platforms. The method adopted in this research is a qualitative approach, which involves data collection techniques such as in-depth interviews, observation, and document analysis. The research results reveal that the use of online learning platforms is able to make a significant contribution to increasing interactivity, flexibility and accessibility in the learning process in the vocational college environment. However, most of the success in this implementation is influenced by several key factors, including adequate infrastructure readiness, lecturer competence in using technology, and effective administrative support. By implementing these strategies in a holistic and integrated manner, it is hoped that vocational colleges can maximize the potential of technology-based learning to improve the quality of their education and teaching.